A new coruleoellagic acid derivative from stems of Rhodamnia dumetorum. Issue 14 (18th July 2018) - Lakornwong, Waranya; Kanokmedhakul, Kwanjai; Kanokmedhakul, Somdej
Abstract: A new coruleoellagic acid derivative, 3, 3′, 4, 4′, 5′-pentamethylcoruleoellagic acid (1 ) together with nine known compounds, hexamethylcoruleoellagic acid (2 ), 3, 4, 3′-tri- O -methylellagic acid (3 ), heptaphylline (4 ), 7-methoxymukonal (5 ), dentatin (6 ), sinapaldehyde (7 ), gallic acid (8 ), 2, 6-dimethoxy-4H-pyran-4-one (9 ) and β -sitosterol (10 ) were isolated from the stems of Rhodamnia dumetorum . Their structures were identified by physical and spectroscopic data (IR, 1D and 2D NMR, and MS). Compounds1, 2 and7 -10 were tested for antibacterial activity against six pathogenic bacterial strains ( Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica serovar Typhimurium, Staphylococcus aureus, and Methicillin resistant S. aureus (MRSA)). Abstract :